Оптимизация геометрических параметров антенной системы для сушки шерсти - Мороз, Александр Николаевич (Eastern-European Journal of Enterprise Technologies, 2014)
A calculation over of geometrical parameters of the aerial system is brought for providing of the set diagram of orientation at drying of wool.